2022
DOI: 10.3389/fvets.2022.977457
|View full text |Cite
|
Sign up to set email alerts
|

Long-term daily feeding of cannabidiol is well-tolerated by healthy dogs

Abstract: Cannabidiol (CBD) containing dog food and treats are widely commercially available, mirroring the growing popularity of CBD as a supplement for humans. Despite this, experimental evidence of the safety and efficacy of long-term oral exposure in dogs is lacking. The purpose of this study was to address the gap in knowledge around the longer-term suitability and tolerance of a broad-spectrum CBD (THC-free) distillate in clinically healthy dogs. The study was a randomized, placebo-controlled, and blinded study wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 55 publications
3
41
1
Order By: Relevance
“…A blinded, parallel design study was conducted at the Waltham Petcare Science Institute to determine the anxiolytic effects of CBD in parallel with a long-term safety study (40). Over this 6 month study dogs were given daily administration of CBD and indicators of stress were measured following exposure to acute and chronic stress-inducing events.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A blinded, parallel design study was conducted at the Waltham Petcare Science Institute to determine the anxiolytic effects of CBD in parallel with a long-term safety study (40). Over this 6 month study dogs were given daily administration of CBD and indicators of stress were measured following exposure to acute and chronic stress-inducing events.…”
Section: Methodsmentioning
confidence: 99%
“…Dogs were weighed to establish an accurate dose of CBD relative to individual bodyweight. The targeted oral dose for each dog was 4 mg/kg bodyweight with an acceptable range of 3.38-4.44 mg/kg bodyweight (40). This study was approved by the Waltham Animal Welfare and Ethical Review Body (80265) and conducted under the authority of the Animals (Scientific Procedures) Act 1986.…”
Section: Animals and Husbandrymentioning
confidence: 99%
See 1 more Smart Citation
“…The elevation of liver values in this cohort, particularly ALP, is consistent with previous reports in human, murine, and canine literature, and thought to be due to induction of cytochrome p450 mediated oxidative metabolism ( 9 , 14 , 15 , 19 , 24 26 ). In a recent trial in dogs receiving 4 mg/kg daily of CBD for 6 months, similar rises in ALP were identified which returned to baseline within 4 weeks of cessation of CBD ( 31 ). However, elevation of liver enzymes is inconsistent in the literature, with multiple reports in canine patients having no identified changes, particularly in young healthy cohorts ( 6 , 8 , 15 ).…”
Section: Discussionmentioning
confidence: 85%
“…While no benefit was identified in this present study, interestingly a recent abstract using the same product used in this study at a 5 mg/kg dose every 8 h may decrease pain scores in patients undergoing intervertebral disk disease surgery ( 30 ). Currently, no toxic dose has been established with reports of 20 mg/kg orally every 12 h for 6 weeks, 4 mg/kg once daily for 6 months, and lower doses of 2 mg/kg every 12 h for 12 weeks being tolerated in dogs ( 19 , 28 , 31 ).…”
Section: Discussionmentioning
confidence: 99%